The transformation cycle of the adaptive system of vocational training of Masters in management of educational institutions - Yeriomenko, O. (Problems of Engineer-Pedagogical Education, 2019)
The article is devoted to the study of the adaptive system of professional training of master‟s students specializing in management of educational institutions. The study proves the necessity of transition from the traditional system of training Master‟s degree students to the new adaptive one, which makes it possible to create a favorable environment for their professional and personal development, acquisition of experience of substantive activity, communication, self-knowledge, and self-organization. The article considers the concepts of "pedagogical system", "educational system", "adaptability", and "adaptive pedagogical system". The features of the adaptive system of Master‟s degree training, its purpose and content are singled out. The article presents the cycle of transformation of the adaptive system of training Master‟s degree students specializing in management of educational institutions, which includes five consecutive stages. With each new task, the cycle is repeated. At the presented stages of the transformation of the adaptive system of Master‟s degree training there is an algorithm for specific actions that create an adaptive educational environment and lead students to achieve the goal, provide an individual growth vector aiming at self-organization and self-development. The author suggests creating models of adaptive behavior of Master‟s students specializing in management from the virtual position of a manager (management mix). The author states that due to such management mix, an individual adaptive script for Master‟s training is created, but each student chooses the script that suits him/her more personally, according to the situation, and is able to “customize” it. The process of functioning of the adaptive system of training of Masters specializing in management of educational institutions has proved the necessity of conducting monitoring research with the help of the development of special measuring tools in the form of qualimetric models which allow tracing the effectiveness of studying a separate topic or training master‟s students during the semester. The results of monitoring the efficiency of the transformation cycle of the adaptive system of training Master‟s students specializing in management of educational institutions confirm the two-way and cyclic nature of the adaptation: " educational system → individual characteristics of students" and "students → educational system", which results in their qualitative personal changes which influence – yet again – changes in the environment.